1989
DOI: 10.1002/ajpa.1330800406
|View full text |Cite
|
Sign up to set email alerts
|

Hamann‐Todd collection aging studies: Osteoporosis fracture syndrome

Abstract: The study presents a retrospective analysis of distal radius, proximal femur, vertebral, and sacral fractures that occurred in 938 Hamann-Todd Collection skeletons. Individuals included in the investigation were retrieved from dissecting room cadavers in Cleveland, Ohio, between the years 1910 and 1940. Demographic analysis showed that the mean ages at death for blacks and whites included in the study were 41.9 and 53.8 years, respectively. Evaluations of fracture repair status were made for all fractures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
0
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 73 publications
2
66
0
3
Order By: Relevance
“…First peak is between ages 5 to 14, the second in males under 50 years of age and the third peak is in females over the age of 40 years [3][4][5]. There is a growing incidence of these fractures in all the three groups with significant increase in elderly females and younger adult males [4][5][6]. It is suggested that the two peaks represent two very different injury patterns: 1) An insufficiency fracture in elderly females [7]; 2) Traumatic injury in younger males.…”
Section: Introductionmentioning
confidence: 99%
“…First peak is between ages 5 to 14, the second in males under 50 years of age and the third peak is in females over the age of 40 years [3][4][5]. There is a growing incidence of these fractures in all the three groups with significant increase in elderly females and younger adult males [4][5][6]. It is suggested that the two peaks represent two very different injury patterns: 1) An insufficiency fracture in elderly females [7]; 2) Traumatic injury in younger males.…”
Section: Introductionmentioning
confidence: 99%
“…Given the association of enthesial reaction with renal bone disease (hyperparathyroidism and osteomalacia) [41,42], hypertrophic osteoarthropathy [43], and syphilis [4,14,44], individuals with those diagnoses were excluded from the comparative sample designated as healthy. The health of the individuals studied was not distinguishable from that of contemporary living populations [31,45].…”
Section: Methodsmentioning
confidence: 74%
“…Two European collections from documented cemeteries were studied: Conchada Cemetery, Coimbra, Portugal [30]; Spitalfields Cemetery, London, Great Britain [31]. We observed individuals from European origins of the Hammann-Todd collection, Cleveland, USA [32] and subjects with an African origin of the Dart collection, Johannesburg, South-Africa. The number of individuals in each collection according to sex are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%